The Philippines and the law of the sea a collection or articles, statements, and speeches - Tolentino, Arturo M. ((Series One Monograph No.5), 1982)
Distribution statement from label mounted on t.p."First published in Philosophical transactions of the Royal Society of London: part A in series A, volume 291 ... part B in series B, volume 284."Includes bibliographies and indexes.